Pengaruh Sarana Dan Prasarana Pembelajaran Seni Budaya Terhadap Hasil Belajar Siswa Di Kelas VIII SMP Negeri 4 Kota Pariaman - Windy Rezkia Julita; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2020)
This study aimed to describe the learning facilities and infrastructure in the field of arts and culture, describe the students’ achievements of participants studying art and culture, and analyze the influence of learning facilities and infrastructure of art and culture on student learning outcomes at 8th Grade Level of SMP Negeri 4 Kota Pariaman. This type of research was qualitative research using descriptive methods. The object of this study was students of 8th Grade Level of SMP Negeri 4 Kota Pariaman who took part in learning vocal techniques. Techniques of data collection were carried out employing literature study, observation, interviews and documentation studies. Techniques of data analysis were through the process of data collection, data reduction, data presentation, and concluding.The results of the study found that the availability of facilities and infrastructure for learning arts and culture in SMP Negeri 4 Pariaman is still incomplete so that in the learning process, especially when practicing with cultural arts equipment, not all students can have practice experience. The allocation of funds from schools for the completeness of cultural arts learning facilities and infrastructure is still low so that the school approves not all planning for the provision of cultural arts learning infrastructure facilities. Student learning outcomes in arts and culture subjects have not reached the expected target because there are still many students who score below the KKM. To overcome the constraints in the limited availability of facilities and infrastructure for learning arts and culture, teachers have sought to improve the active role of students in adding insight by accessing internet media and also adding additional learning hours to anticipate the limitations of practice time due to inadequate cultural arts equipment available.